Prosedur Pengembalian dan Pemulihan Kerugian Negara Akibat Tindak Pidana Korupsi - Sandi Herintus Kabba; I Made Arjaya; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
Corruption is an extraordinary crime whose eradication must be carried out in an extraordinary manner according to the procedures for returning and recovering state losses due to corruption. The purposes of this study are to reveal the process of implementing the return and recovery of state losses by prosecutors on corruption crimes as well as efforts to restore and recover state losses due to corruption. The method used is normative legal research with a statutory approach and a conceptual approach. The technique of collecting legal materials is done through the study of recording and documentation. Primary and secondary sources of legal materials are used as sources of legal materials in this study. Then, the legal materials and data are managed using interpretation analysis. The results of the study reveal that the procedure for returning and recovering state losses due to corruption is in accordance with the procedures, namely the Law on the Eradication of Corruption and other regulations. efforts to recover and recover state losses due to corruption by maximizing the return of state losses by confiscation, tracing the assets of the convict, the authority of the KPK prosecutor must be regulated firmly and clearly. The author suggests that the Government should provide adequate facilities and infrastructure for the Prosecutor's Office and the KPK in order to maximize the eradication of corruption, the public needs to submit information to the Prosecutor's Office, the KPK, and the Police regarding corruption crimes that have occurred.